Effects of Anxiety and Learning Styles on Foreign Language Testing: Case of Work-Study Contract Students - karine LONGIS MCMILLAN (Universitas Ahmad Dahlan, 2021)
Studies have proved multiple times that anxiety and different learning styles within the FL classroom affect students when they are doing a test. These studies however have not yet observed every different kind of students. With this context, data were collected from 71 work-study contract vocational higher diploma students from EFIATP Correze, France during the 2020-2021 academic years. As a conclusion of this study, it is determined that there are no significant relationships between the FL student anxiety in the classroom, their learning styles and their test Level.Keywords: FLÂ , foreign languageÂ , anxiety, learning styles, test level, work-study contract Â students